2022
DOI: 10.1002/smll.202202564
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Photothermal‐Pyroelectric Biosensor for Rapid and Point‐of‐Care Diagnosis of Acute Myocardial Infarction: A Convergence of Theoretical Research and Commercialization

Abstract: Acute myocardial infarction (AMI) survivors face a high risk of mortality as a result of increasing heart failure and irreparable myocardial injury. New portable methods for immediate diagnosis must be developed to provide patients with daily warnings. Herein, the development of a dual‐mode photothermal‐pyroelectric output system based on a point‐of‐care platform for rapid AMI detection is reported. Termed as Integrated Photothermal‐Pyroelectric Biosensor for AMI (IPPBA), the method leverages cascade enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Evidence from the scientific literature has revealed that cardiac biomarkers, e.g., myoglobin, B-type natriuretic peptide, heart-type fatty acid binding protein (h-FABP), and cardiac troponin I (cTnI), can provide a rapid diagnosis of AMI. However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, , chemiluminescence, photothermal biosensing, , and electrochemical detection. Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research. Currently, developing unique signal-on sensing mechanisms is a significant research branch in PEC bioanalysis due to their reduced background signals and high sensitivity. Therefore, the development of a signal-on amplified PEC bioanalysis for AMI biomarker detection is highly desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the scientific literature has revealed that cardiac biomarkers, e.g., myoglobin, B-type natriuretic peptide, heart-type fatty acid binding protein (h-FABP), and cardiac troponin I (cTnI), can provide a rapid diagnosis of AMI. However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, , chemiluminescence, photothermal biosensing, , and electrochemical detection. Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research. Currently, developing unique signal-on sensing mechanisms is a significant research branch in PEC bioanalysis due to their reduced background signals and high sensitivity. Therefore, the development of a signal-on amplified PEC bioanalysis for AMI biomarker detection is highly desirable.…”
mentioning
confidence: 99%
“…1−5 However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, 6,7 chemiluminescence, 8 photothermal biosensing, 9,10 and electrochemical detection. 11−13 Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research.…”
mentioning
confidence: 99%
“…The thermochromic test protocol for the target cTnI was obtained by drawing on some of our previously reported studies. , In this work, the target signal is converted into detectable temperature and colorimetric signals by using the 3,3′,5,5′-tetramethylbenzidine (TMB) probe with good photothermal response as a signal transduction tag, and the grayscale values are recorded on a portable smartphone. The classical sandwiched immunoreaction was used to capture and signal transduce the target protein cTnI in whole blood, as detailed in this section in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the unique and efficient photothermal conversion properties, photothermal effects have attracted great repercussions in various fields of research, including photothermal therapy and photothermal power catalysis. Interestingly, as an emerging principle of signal transduction, sensors based on the photothermal effect have been successfully constructed for the visualization of biosignal readouts. The construction of efficient probes through photothermal reagents, including melanin-like, , oxidation products of TMB, and photothermal nanoparticles (NPs), provides a new vision for the construction of efficient biosensors. For example, Fu et al developed a series of photothermal effect-based microfluidic platforms for the integration and visualization of target immune signals. , In previous work, we integrated an efficient photothermal biosensing technology for the detection of low-abundance target proteins, and more critically, its output mode was extended to photothermal coupling to boost its sensitivity even further. , Despite our efforts to develop more delicate photothermal biosensing platforms, the photothermal transmitter output still relies on portable thermal imagers, which has an expense in constructing the complete photothermal device.…”
mentioning
confidence: 99%
See 1 more Smart Citation